2013
DOI: 10.1007/s11483-013-9295-2
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition and Water Dynamics in Hyaluronic Acid Hydrogels

Abstract: , J.; A. Kyritsis; Monleón Pradas, M.; Vallés Lluch, A.; Gallego Ferrer, G.; P. Pissis (2013). Glass transition and water dynamics in hyaluronic acid hydrogels. Food Dielectric measurements contribute to the study of the molecular dynamics of water at biological interfaces, in the case of several biomolecules, such as polysaccharides [14] and hydrated proteins [15][16][17][18][19] and also in the case of synthetic hydrogels [20]. In the case of hydrated proteins, it has been shown that the observed dynamics d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…On the one hand, this suggested that SAP was not reversible in terms of humidity sorption/desorption, and that water molecules were not easily detached from it, perhaps because of their condensation among the hydrophobic skeleton of the drug. On the other hand, MS formulations (panels (b) and (c)) showed, as previously observed for native HA [67,68], similar trends for their sorption and desorption ramps, and high water-binding capacity due to H-bonds and electrostatic interaction with hyaluronan hydroxyl and carboxylic groups, respectively. Two-stages moisture sorption processes occurred for hyaluronan MS formulations, and this was in agreement with data already reported in the literature for native HA [67,68].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…On the one hand, this suggested that SAP was not reversible in terms of humidity sorption/desorption, and that water molecules were not easily detached from it, perhaps because of their condensation among the hydrophobic skeleton of the drug. On the other hand, MS formulations (panels (b) and (c)) showed, as previously observed for native HA [67,68], similar trends for their sorption and desorption ramps, and high water-binding capacity due to H-bonds and electrostatic interaction with hyaluronan hydroxyl and carboxylic groups, respectively. Two-stages moisture sorption processes occurred for hyaluronan MS formulations, and this was in agreement with data already reported in the literature for native HA [67,68].…”
Section: Resultssupporting
confidence: 79%
“…On the other hand, MS formulations (panels (b) and (c)) showed, as previously observed for native HA [67,68], similar trends for their sorption and desorption ramps, and high water-binding capacity due to H-bonds and electrostatic interaction with hyaluronan hydroxyl and carboxylic groups, respectively. Two-stages moisture sorption processes occurred for hyaluronan MS formulations, and this was in agreement with data already reported in the literature for native HA [67,68]. Indeed, in response to RH increment from 0 to 60%, water uptake slowly increased up to 20.9% for HA MS, 14.2% for HA–SAP MS, 16.4% for HA-CL MS, 23.0% for HA-CL–SAP MS (changes in mass similar to that of SAP (+ 17.8%) at 60% RH).…”
Section: Resultssupporting
confidence: 79%
“…However, the T g values of both of the WF and PF composites decreased slightly when the fiber content increased from 10% to 40%. This is probably because of the presence of a low fraction of cellulose fibers that contain polar groups (such as hydroxyl groups), and the electrostatic repulsion between these polar groups increased the distance between molecular chains and resulted in a decrease in T g . The crystallinity values ( X c ) of the WF and PF composites increased compared to that of the PLA matrix (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The water content from topical humectants can quickly evaporate from the warm skin surface, depending on the influence of RH and temperature, leaving a dehydrated product film along with HA and other nonvolatile ingredients. Others have pursued improving topical humectant performance by modifying HA through covalently bonded cross‐linking structures and covalently bonded hydrophobic modifications (e.g., AcHA) . Although these altered forms of HA do offer superior hydration benefits compared to traditional linear HA, they do not combine both properties of improved water binding by cross‐linking with improved affinity to the skin's surface through hydrophobic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Others have pursued improving topical humectant performance by modifying HA through covalently bonded cross-linking structures and covalently bonded hydrophobic modifications (e.g., AcHA). 19,20,22,23,34,35 Although these altered forms of HA do offer superior hydration benefits compared to traditional linear HA, they do not combine both properties of improved water binding by cross-linking with improved affinity to the skin's surface through hydrophobic modifications. However, we theorized water and binding water more tightly in comparison to the commercial HA-containing benchmark.…”
Section: Discussionmentioning
confidence: 99%